Grade Improvement by Academically Endangered Student-Athletes Following Brief Study Skills Training - Fletcher, Harold J.; Mand, Brian (My University, 1988)
Ten academically endangered male student-athletes were offered 10 two-hour classes designed to train college study skills (memory techniques, taking notes from texts and lectures, and preparing for and taking exams). Attendance was voluntary. Six attended regularly, tried to learn the skills, and subsequently (in their concurrent courses) a semester GPA which was a full letter grade above their cumulative GPA prior to the training. Statistically, this GPA gain was significantly higher than was the slight loss shown by the four who did not attend regularly and did not try to learn these study skills. It was recomended that all entering student-athletes be given training in effective study skills before academic problems arise.
Keywords: skills; at-risk; academic performance